ANALISIS PENDAPATAN USAHA TEMPE BUNGKUS DAUN DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Indah Novita Dewi; Nila Kusumawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
The leaf-wrapped tempe business in almost all regions in Kalimantan has not taken into account the costs incurred during the production process which has an impact on not taking into account the income obtained from the business carried out so it is necessary to analyze the business income of leaf-wrapped tempe, whether it is profitable or detrimental to the producer so that the business needs to be developed/continued or even vice versa.The purpose of this study was to determine the income and profitability of the leaf-wrapped tempe business in Loa Kulu District, Kutai Kartanegara Regency. This research was conducted for approximately three months, from November 2019 to February 2020 in Loa Kulu District, Kutai Kartanegara Regency. Sampling taken in this study was carried out by Snowball Sampling. The result showed that the income received by all respondents in Loa Kulu District, Kutai Kartanegara Regency was Rp14.851.187,53/month and the average income was Rp2.121.598,22/month; and the resulting R/C ratio value of 1,20 means that the leaf wrap tempe business is profitable or feasible continue.